MENCIPTAKAN KOTA CERDAS: MEMANFAATKAN AI (ARTIFICIAL INTELLIGENCE) UNTUK PENGEMBANGAN RUANG PUBLIK PERKOTAAN YANG CERDAS - Sriany Ersina (Universitas Negeri Makassar, 2023)
As cities continue to grow and face increasing challenges, the concept of smart cities has emerged as a solution to create sustainable, efficient, and livable urban environments. One crucial aspect of smart cities is the development of intelligent urban public spaces that cater to the diverse needs and preferences of residents and visitors. This paper explores the role of AI in the development of such spaces, focusing on how AI technologies can enhance their design, functionality, and user experience. It examines the application of AI in areas such as data analytics, user behavior analysis, sensor networks, and adaptive systems to create dynamic and responsive public spaces. Furthermore, it discusses the benefits, challenges, and potential ethical considerations associated with harnessing AI for intelligent urban public spaces development. Through this exploration, the paper highlights the transformative potential of AI in shaping the future of urban environments and fostering inclusive and sustainable communities.